PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA, MOTIVASI KERJA TERHADAP KINERJA PEGAWAI (BPBD KABUPATEN EMPAT LAWANG) - Erdi Satria Novrata; Ade Tiara Yulinda (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2023)
The purpose of this study was to determine the effect of leadership style on employee performance, work discipline on employee performance, work motivation on employee performance, and the influence of leadership style, work motivation, work discipline simultaneously on the performance of BPBD employees at Empat Lawang Regency. This research method is associative and data collection by observation, interviews and questionnaires. The population in this study were 38 employees, the data analysis method was "validation test, reliability test, classical assumption test, normality test, heteroscedasticity test, multicollinearity test, multiple regression analysis, f-test, and t-test, and hypothesis testing. "The results showed multiple linear regression of Y=.335(x1)=.324(x2)+.497(X3)+e, where the constant value (a)=.410 . While the -F test (simultaneous) where the significant value is 0.000 <0.05, which means that leadership style, work discipline, work motivation have a positive and significant effect on the performance of BPBD employees in Empat Lawang Regency. In the (partial) t-test of the leadership style variable (X1), t count (3.088) > (3.001954) means that it has an effect on employee performance variables, a significant level of 0.004 < 0.005 indicates leadership style has a positive and significant effect on performance, and work discipline (X2) partially t count (3.559) > (3.001954) and a significant level of 0.001 < 0.005 indicating that the work discipline variable has a positive and significant effect on the performance variable. While work motivation (X3) (6,343) > (3.001954) and significant 0.000 > 0.005 which means that the variable of work motivation has a positive and significant effect on performance. It can be concluded that leadership style (x1) work discipline (x2) and work motivation (X3) simultaneously and partially have a positive and significant effect on the performance (Y) of BPBD employees in Empat Lawang Regency. Keywords: Leadership Style, Discipline, Work Motivation and Performance